2020
DOI: 10.1002/dmrr.3334
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and metabolic effects of metformin added to insulin therapy in patients with type 1 diabetes: A systematic review andmeta‐analysis

Abstract: Background The incidence of type 1 diabetes mellitus (T1DM) is increasing among youth worldwide, translating to an increased risk ofearly‐onset cardiovascular disease (CVD). Mounting studies have shown that metformin may reduce maximal carotidintima‐media thickness (cIMT), improve insulin resistance and metabolic control in subjects with T1DM, and thus, may extend cardioprotective benefits. This systematic review and meta‐analysis was performed to assess the efficacy and safety of metformin added to insulin th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 50 publications
1
21
0
2
Order By: Relevance
“…Metformin has been evaluated in numerous small trials in people with type 1 diabetes with hopes that its insulin-sensitising properties would improve glycaemic management and/or reduce cardiovascular risk [ 244 , 245 ]. The largest study to date assessed the use of metformin 1 g, twice daily, in 428 people with type 1 diabetes who were treated for 3 years, with a primary endpoint of changes in mean carotid intima–media thickness, a marker of cardiovascular disease risk.…”
Section: Section 13: Adjunctive Therapiesmentioning
confidence: 99%
“…Metformin has been evaluated in numerous small trials in people with type 1 diabetes with hopes that its insulin-sensitising properties would improve glycaemic management and/or reduce cardiovascular risk [ 244 , 245 ]. The largest study to date assessed the use of metformin 1 g, twice daily, in 428 people with type 1 diabetes who were treated for 3 years, with a primary endpoint of changes in mean carotid intima–media thickness, a marker of cardiovascular disease risk.…”
Section: Section 13: Adjunctive Therapiesmentioning
confidence: 99%
“…These results align well with previous research on youth with T1DM ( 16 ). In contrast, conflicting conclusions were reported by Liu et al who found improvement in partial lipid profiles and diastolic blood pressure in T1DM patients with additional metformin ( 24 ).…”
Section: Discussionmentioning
confidence: 92%
“…According to the previous literature, metformin supposedly increases the risk of gastrointestinal adverse effects and may induce more hypoglycemia events in patients with T1DM ( 24 , 40 ). In the present study, no severe adverse events were observed, and only four participants (11.8%) in the metformin group had the insulin dose thereof down escalated due to gastrointestinal side effects.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations